A comparison of the immunofluorescent with histochemical and biological test in the diagnosis of rabies - Silva, Renato Augusto da; Silva, Norma Moraes da; Guimarães, Romeu Soares (Pesquisa Agropecuaria Brasileira, 2014)
A comparison was made of the efficiency of the fluorescent antibody technique, Negri body examination and mouse inoculation test for the detection of rabies. The brains from four hundred and sixty one rabies suspect animals and the brain of a man who died of rabies were examined by the methods cited above. Also, 77 submaxillary glands and 63 brains of animals, plus two samples of spinal fluid and one of saliva from human cases suspected of rabies, were examined by the fluorescent antibody technique and mouse inoculation test. The fluorescent antibody technique was comparable in efficiency to the mouse inoculation test and superior to the Negri body examination.